Identifying a causal link between structure and dynamics in supercooled water - Malaspina, David Cesar (2009)
By means of molecular-dynamics simulations we firmly establish the long-awaited existence of strong correlations between structure and dynamics for a glass-forming system: supercooled water. We find molecules with similar structural (and dynamical) properties to be clustered in space, thus reveling the existence of structured regions with low dynamic propensity and unstructured ones with a high-mobility tendency.